Long-term self-reported symptoms and psychophysical tests in COVID-19 subjects experiencing persistent olfactory dysfunction: a 4-year follow-up study - Saccardo, Tommaso; Roccuzzo, Giuseppe; Fontana, Alessandro; Zampollo, Sonny; Scarpa, Bruno; Nicolai, Piero; Pendolino, Alfonso Luca; Mucignat, Carla; Marchese-Ragona, Rosario; Ottaviano, Giancarlo (Frontiers in Neural Circuits, 2025)
BackgroundSince the onset of the COVID-19 pandemic, chemosensory dysfunction (CD), including olfactory and taste quantitative dysfunction (OD/TD), has emerged as a prevalent and early symptom in SARS-CoV-2-infected subjects. This study explores the prevalence, duration, and recovery trajectory of COVID-19-related olfactory dysfunction (C19OD), with a specific focus on the four-year follow-up.MethodsUsing a combination of psychophysical tests (Sniffin’ sticks) and patient-reported outcome measures (sVAS and tVAS), 83 participants were prospectively evaluated for OD and parosmia. Factors influencing long-term olfactory recovery were analysed.ResultsBaseline assessments revealed OD in 56.6% of patients, with progressive improvement observed over 4 years. At the four-year follow-up, 92.3% of patients recovered their olfaction while the remaining still reported hyposmia. Younger age and olfactory training were found to be favourable prognostic factors.ConclusionOur findings show that, despite most individuals with C19OD recover olfaction within the first year, a subset of them continue to experience prolonged CD, demonstrating a slow, constant and meaningful improvement over years. This prolonged recovery period highlights the complexity of SARS-CoV-2’s impact on olfactory function and highlights the need of further research on CD pathophysiology with the aim to improve therapeutic approaches to C19OD.